Private sector development in the South and East Mediterranean region - Richard Woodward; Mehdi Safavi (Center for Social and Economic Research (CASE), 2012)
This report is concerned with the analysis of privatization and private sector development for the eastern and southernMediterranean countries partnered with the European Union and collectively known as MED-11. Noting that the analysis applies to the situation prior to the dislocations of the Arab Spring, we review the shift in the relative shares of the public and private sectors in these countries, as well as the business climate affecting the development of the private sector, examine a number of cultural factors that may influence the development of the private sector, and discuss some alternative scenarios for future developments. In the last 20 years, efforts have been made in all countries of the MED-11 to encourage private sector development and, to a greater or lesser extent, privatization of stateowned assets. However, there is a great deal of differentiation among the countries in the group. In the MED-11, Israel has not only the most business-friendly policy environment but also the most developed private sector, accounting for almost 80% of employment. The other countries of the region can be divided into two groups: one, including Algeria, Libya, and Syria, where reforms promoting privatization and private sector development have been very limited, and the rest, in which they have been much more extensive (the Palestine Authority is, for obvious reasons, a rather special case). A generally poor business environment makes for a large informal sector in almost every country in the region; however, generally speaking, we do not find the cultural factors we examine to be hostile to private sector development. Optimistic, reference and pessimistic scenarios are discussed; which of these is realized in any particular MED-11 country will depend greatly on the direction of change following the events of 2011's Arab Spring.
Keywords: L32; L33; L50; O16; O17; P33; 330; Private Sector; Privatization; Business Climate; Middle East; North Africa; Privatwirtschaft; Privatisierung; Geschäftsklima; Mittlerer Osten; Nordafrika; Mittelmeerraum